In Britain 21st century edition - Vaughan-Rees M. Michael (London, Chancerel, 2000)
In Britain is the authentic introduction to British civilisation and everyday English language. This fully up-to-date 21st Century Edition enables students to practise all four language-learning skills. The main reading-practice section includes pre-reading questions, comprehension exercises and speaking activities. It covers every aspect of Britain at the beginning of the new millennium, with over 40 topic headings, including classic and contemporary English literature, the media, economics, the environment and employment. For students visiting Britain, there is useful information about daily life, transport, London and the regions. The Workbook section contains follow-up listening, speaking, and writing exercises.